2014
DOI: 10.7150/jca.9726
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal and Prostate Cancer Risk in Diabetes: Metformin, an Actor behind the Scene

Abstract: Both diabetes and cancer are prevalent diseases whose incidence rates are increasing worldwide, especially in countries that are undergoing rapid industrialization changes. Apparently, lifestyle risk factors including diet, physical inactivity and obesity play pivotal, yet preventable, roles in the etiology of both diseases. Epidemiological studies provide strong evidence that subjects with diabetes are at significantly higher risk of developing many forms of cancer and especially solid tumors. In addition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 81 publications
0
34
0
2
Order By: Relevance
“…10,11) Finally, a recent study suggested statin use moderates the risk of prostate cancer among type II diabetic patients using metformin.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…10,11) Finally, a recent study suggested statin use moderates the risk of prostate cancer among type II diabetic patients using metformin.…”
Section: )mentioning
confidence: 99%
“…7) Further, epidemiologic evidence revealed a decreased incidence of prostate cancer in men taking metformin, 8,9) and both animal and in vitro models demonstrate its activity in prostate cancer cell lines. 10,11) Finally, a recent study suggested statin use moderates the risk of prostate cancer among type II diabetic patients using metformin. 12) Epidemiological studies have shown a reduced risk of advanced prostate cancer with the use of statins.…”
mentioning
confidence: 99%
“…Of importance, the risk of developing these tumor types is significantly higher in patients with type 2 diabetes. Lifestyle risk factors, including diet and obesity, play relevant roles in the etiology of both diseases (2). In fact, it has been recently reported that a high-fat diet and obesity increased the development and aggressiveness of breast cancer tumors in vivo and that the oral administration of FTY720 (fingolimod) suppressed these effects (3).…”
mentioning
confidence: 99%
“…Thus, the antidiabetes drug metformin has been described to induce PP2A activity and potent antitumor effects in colorectal and prostate cancer, among others (2,8). However, a recent study reported that metformin could increase the risk of tauopathies in elderly patients with diabetes (9).…”
mentioning
confidence: 99%
“…Diversos estudos clínicos apontaram para associação entre o uso de metformina e a redução e prevenção na progressão em diferentes tipos de câncer (7,(59)(60)(61)(62)(63)(64)(65)(66) intrinsecamente observado nos tumores com mutações nas subunidades de SDH (succinato desidrogenase), pode representar um mecanismo interessante, cuja eficiência alvo direcionada merece ser melhor esclarecida.…”
Section: Efeito Da Associação De Metformina E Sunitinib Sobre a Viabiunclassified